Can surgical treatment be justified for neuroendocrine carcinoma of the gallbladder?. Issue 11 (March 2019) - You, Yung Hun; Choi, Dong Wook; Heo, Jin Seok; Han, In Woong; Choi, Seong Ho; Jang, Kee-Taek; Han, Sunjong
Abstract : Abstract: Clinical features and treatment of GB neuroendocrine carcinoma (GB-NEC) are not well understood. This study aimed to analyze clinical outcomes of GB-NEC and verify the oncologic benefit of surgical treatment. From October 1994 to December 2014, the medical records of 31 patients with GB-NEC at a single center were retrospectively reviewed. There were 18 inoperable cases due to distant metastasis, including 7 of best supportive care (Tx.1) and 11 of non-operative palliative treatment (Tx.2). 4 patients received non-curative, palliative resection (Tx.3). Only 9 patients were able to undergo curative-intent resection (Tx.4). Among the 31 patients with GB-NEC, preoperative mean value of carbohydrate antigen 19-9 (CA 19-9) was 74.8 ± 156.1 U/mL and the median overall survival time was 10 months (range 7.0-12.0 months). Of these, 21 (67.7%) patients received systemic treatment. Among 9 patients who underwent curative-intent resection (Tx.4), 9 patients had poorly differentiated cancer cells and 7 patients received radical cholecystectomy. 6 patients had adjuvant treatment including concurrent chemoradiation therapy (CCRT) or chemotherapy alone. The recurrence rate was 88.9%. The median overall survival between 4 groups was as follows: 4.0 (3.0–18.0) months in Tx.1 (n = 7) versus 9.0 (3.0–21.0) months in Tx.2 (n = 11) versus 11.0 (3.0–15.0) months in Tx.3 (n = 4) versus 23.0 (8.0–34.0) months in Tx.4 (n = 9), respectively. Significant differences in median overall survival time existed between Tx.2 and Tx.4; 9 (3.0–21.0) months versus 23.0 (8.0–34.0) months ( P  = .017). Most GB-NECs show poor biologic behavior. Nonetheless, curative-intent resection could possibly promote longer survival than other treatment modalities for GB-NEC. Efforts to undergo curative resection through early detection and development of adjuvant treatment are needed.